Late-onset presentation of POLG1-associated mitochondrial disease. Issue 3 (31st March 2019) - Meira, Bruna; Roque, Rafael; Pinto, Miguel; Caetano, André
Abstract : Mutations in the nuclear POLG1 gene compromise the integrity of mitochondrial DNA and show great allelic and clinical heterogeneity. Among adult POLG1-associated mitochondrial disease, the main clinical feature is chronic progressive external ophthalmoplegia. Other related clinical manifestations are sensory or cerebellar ataxia, peripheral neuropathy, myopathy or extrapyramidal symptoms. We report the case of a 72-year-old man who presented with a late onset sensory neuronopathy, chronic progressive external ophthalmoplegia, gait ataxia and parkinsonism. Genetic studies showed a compound heterozygosity of known pathogenic mutations in the POLG1 gene (variant T252I/P587 L in cis configuration in allele 1 and variant R807C in allele 2). Late life presentation highlights that mitochondrial disorders should be considered regardless of age of onset of symptoms.